Supramolecular organization-electrical properties relation in nanometric organic films - Alessio, Priscila [UNESP]; Braunger, Maria Luisa [UNESP]; Aroca, Ricardo Flavio; Olivati, Clarissa de Almeida [UNESP]; Leopoldo Constantino, Carlos Jose [UNESP] (Amer Chemical Soc, 2015)
The need to improve the performance of electronic devices based on organic materials has been at the center of Structure property relation research, where the main objective is to develop low cost and flexible electronic components in large-scale. Important contributions, to the performance of such devices have been made based on studies of the supramolecular organization of small organic molecules, primarily those with pi-conjugated systems. Here we examine the relationship of supramolecular organization and the electrical properties of a substituted perylene tetracarboxylic diimido in nanometric films fabricated by physical vapor deposition (PVD). The morphology of the thin solid films is probed with optical and electron microscopy and the supramolecular characterization includes vibrational and electronic spectroscopies. They electrical properties are studied using AC and DC measurements with interdigitated electrodes and diode-like structures. A higher conductivity is observed when measured with the diode-like structure. It seems to be associated with a perpendicular orientation of the electric field with respect to the pi-pi molecular Stacking, favoring the charge transport through these pi aggregates. The results enhance the understanding of organic electronics, helping surface engineering to harness supramolecular organization to improve performance of thin film devices.